2023
DOI: 10.1155/2023/2180923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arterial Stiffness and Its Relation to Innovative Anthropometric Indices in Persian Adults

Abstract: Background. BMI has been evaluated as an old criterion to evaluate obesity in individuals, but it does not assess abdominal obesity and lean mass. We aimed to evaluate the possible relationship of new anthropometric indices (namely, a body shape index (ABSI), the body roundness index (BRI), the visceral adiposity index (VAI), the visceral fat area (VFA), and waist-hip ratio (WHR)), with one of the known critical factors of atherosclerosis, arterial stiffness. Methods. Overall 5921 individuals were enrolled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Furthermore, numerous previous studies have shown that the visceral adiposity index (VAI), which responds to visceral fat, is independently and positively correlated with AS [ 28 30 ]. In a study involving 5921 Persian adults, Zahra et al found that among overweight men and women, as well as obese women, VFA linked better with AS than VAI, BMI, and WC [ 31 ]. The VAI, which includes lipid-related metabolic markers (TG and HDL-C) and anthropometric indices (BMI and WC), is a newly developed visceral fat index that is thought to be able to depict the distribution of fat [ 28 ], but the VFA predicts AS risk better than it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous previous studies have shown that the visceral adiposity index (VAI), which responds to visceral fat, is independently and positively correlated with AS [ 28 30 ]. In a study involving 5921 Persian adults, Zahra et al found that among overweight men and women, as well as obese women, VFA linked better with AS than VAI, BMI, and WC [ 31 ]. The VAI, which includes lipid-related metabolic markers (TG and HDL-C) and anthropometric indices (BMI and WC), is a newly developed visceral fat index that is thought to be able to depict the distribution of fat [ 28 ], but the VFA predicts AS risk better than it.…”
Section: Discussionmentioning
confidence: 99%
“…found that among overweight men and women, as well as obese women, VFA linked better with AS than VAI, BMI, and WC [31]. The VAI, which includes lipid-related metabolic markers (TG and HDL-C) and anthropometric indices (BMI and WC), is a newly developed visceral fat index that is thought to be able to depict the distribution of fat [28], but the VFA predicts AS risk better than it.…”
Section: Discussionmentioning
confidence: 99%